Successful intracranial response of lorlatinib after resistance with alectinib and brigatinib in patients with ALK‐positive lung adenocarcinoma: Implications of CNS penetration rate of brigatinib - Yuki Sato; Yoshiharu Sato; Kei Irie; Shigeki Nanjo; Shigeo Hara; Satoru Fujiwara; Keisuke Tomii (Thoracic Cancer, 2024)
Abstract We present the case of a 34‐year‐old Japanese man with anaplastic lymphoma kinase (ALK)‐positive non‐small cell lung cancer and brain metastases. After central nervous system (CNS) disease progression with alecintib and brigatinib, treatment with lorlatinib resulted in a good intracranial response. In this case, we investigated brain penetration ratio of brigatinib using cerebrospinal fluid and paired serum samples, and the ratio was 0.012. Further, we investigated resistance mechanisms via next‐generation sequencing (NGS) using lung biopsy at lung cancer diagnosis and brain biopsy sample at progressive disease of brigatinib. No apparent resistance mechanism of known ALK resistance, such as ALK mutations, amplifications, epithelial‐mesenchymal transition (EMT) and bypass pathway activation were detected. Taken together, we speculate that the low CNS penetration rate of brigatinib confers CNS progression. Further studies are warranted to reveal the resistance mechanism and propose a treatment strategy for CNS progression in ALK‐positive patients.